Brigade Hassan Bin Tsabit: Netizen Indonesia dalam Perang Media Sosial untuk Dukung Palestina - Windhi Tia Saputra (Journal on Education, 2024)
This research explores the role of the Hassan Bin Tsabit Brigade in utilizing TikTok as a tool of social media warfare in supporting Palestine during the Israel-Palestine conflict. The study employs an online observation method to investigate the activities of the Hassan Bin Tsabit Brigade on the TikTok platform. Systematic online observation was conducted from November 2023 to January 2024, encompassing monitoring accounts related to the Brigade, including posts, comments, and user interactions. This unobtrusive observation approach allows researchers to collect data without direct interaction. The observation focuses on the types of content, posting frequency, interaction patterns, and the Brigade's strategies in disseminating pro-Palestine messages. The research identifies diverse strategies and active interactions by the Brigade to spread pro-Palestine messages. Brigade Commander Erlangga Greschinov plays a key role, sharing accounts considered to support the oppression of Palestine. Significant impacts were also found, including responses from Israel and changes in strategies from IDF accounts on TikTok. These findings prompt reflection on the online activism and the complexities of social media warfare in global conflicts.